Study on mechanical properties of cemented backfill with different mineral admixtures. (27th February 2023) - Qiu, Huafu; Liang, Chao; Tu, Bingbing; Liu, Lang; Zhang, Fushun; Lv, Wenyu
Highlights: Rational use of gob, coal impurities, metal ore smelting waste. The influence mechanism of mineral admixtures on strength and permeability of backfill is studied. The influence of mineral admixtures on the damage deformation of backfill is analyzed. The relationship between microstructure and porosity and permeability is analyzed. Abstract: In order to establish storages in mining goaf, calcium bentonite (Ca-B), slag powder (SP) and silica fume (SF) were added into the backfill to obtain a cemented backfill with high stability and certain anti-seepage function. Uniaxial compressive strength (UCS), porosity, permeability and scanning electron microscopy (SEM) tests were carried out. Results show that SP and SF can significantly improve the strength at the same level of incorporation, the highest increases are 216.37% and 125.51% compared with the control group, while Ca-B has strong swelling and low pozzolanic activity, the strength can only be increased by 32.83%, and the strength can be significantly reduced by 28.34% if the Ca-B content is too high. The incorporation of mineral admixtures can increase the number of closed pores in the compaction stage, and the damage mode of backfill can be changed with the increase of the incorporation amount. There is a power function relationship between permeability and porosity, permeability increases with the increase of porosity. The strong pozzolanic reaction of SP and SF can produce more gel compounds to block pore channels, refine pore size and reduce permeability. Compared with the control group, the permeability can be reduced by 46.05% and 36.84% at the highest, while Ca-B due to strong swelling, low activity, and insufficient reaction cause the backfill porous, and the permeability is greater than the control group under different incorporation amounts.